2016
DOI: 10.1111/afe.12201
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns at host and forest stand scale and population regulation of the pine processionary mothThaumetopoea pityocampa

Abstract: 1 Different spatial processes are likely to generate variability at different scales. Thus, the explanation of patterns may be facilitated by knowledge about the spatial scales where variation in patterns occurs. In the present study, the link between spatial patterns of the pine processionary moth Thaumetopoea pityocampa Den. & Schiff.(Lepidoptera, Notodontidae) at two different scales, as well as its population dynamics, was assessed. 2 First, the spatial patterns of T. pityocampa population were assessed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…can play a significant role in the natural regulation of T. pityocampa and contribute to maintain their populations at low abundance levels within its distribution range (Tarasco et al 2016;Zamoum et al 2017;Rahim and Chakali 2022;Sebti et al 2022;Hein et al 2023;Lagogiannis et al 2023). Pimentel et al (2017) showed that the population density of T. pityocampa decreases dramatically after a year of severe defoliation as a consequence of both activity of the natural enemies and change in food quality (Pimentel et al 2017;Rahim et al 2021;Sebti et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…can play a significant role in the natural regulation of T. pityocampa and contribute to maintain their populations at low abundance levels within its distribution range (Tarasco et al 2016;Zamoum et al 2017;Rahim and Chakali 2022;Sebti et al 2022;Hein et al 2023;Lagogiannis et al 2023). Pimentel et al (2017) showed that the population density of T. pityocampa decreases dramatically after a year of severe defoliation as a consequence of both activity of the natural enemies and change in food quality (Pimentel et al 2017;Rahim et al 2021;Sebti et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, this might not be the case in Portugal, where mild winters offer good climatic conditions for larval development. On the other hand, high nest density at the tree level tends to increase overall mortality of young larvae (Pimentel et al 2017). More, SP larvae are still in the very beginning of their development when WP females lay their eggs, but most SP larvae have reached L4 and L5 instars when WP individuals hatch.…”
Section: Competition Could Be the Driver Of The Observed Parapatrymentioning
confidence: 99%